Bridging the Moral Cognition-Action Gap: An Integrated Ecosystem of Religious Education and Policy in Higher Education - Dilan Imam Adilan; Mu’min Mu’min (Borong Newinera Publisher, 2026)
This article examines religious education as a system of moral education and explores its conceptual relationship with higher education policy in shaping attitudes and behaviors. Drawing on a Systematic Narrative Synthesis (SNS) of multidisciplinary literature in moral education, religious studies, psychology, sociology, and higher education policy, the study addresses a persistent global problem: the gap between moral knowledge and moral behavior among university students. While religious education is widely expected to cultivate ethical character, empirical and conceptual studies repeatedly demonstrate that moral cognition does not automatically translate into consistent moral conduct. At the same time, higher education institutions increasingly rely on formal policies codes of ethics, integrity systems, and violence-prevention frameworks to regulate behavior. This study synthesizes the literature to conceptualize religious education as an internal moral formation system and policy as an external moral-regulatory mechanism. The synthesis identifies three dominant relational models between religious education and policy: complementary, overlapping, and tension based. Using Indonesia as an illustrative case, the article argues that effective moral formation in higher education requires an integrated moral–regulatory ecosystem rather than a substitution of education by policy or vice versa. The study contributes a theoretically grounded framework for understanding how attitudes and behaviors are formed and regulated in contemporary higher education.